The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.3390/ijms18112282
|View full text |Cite
|
Sign up to set email alerts
|

Refined Deep-Sea Water Suppresses Inflammatory Responses via the MAPK/AP-1 and NF-κB Signaling Pathway in LPS-Treated RAW 264.7 Macrophage Cells

Abstract: Atopic dermatitis (AD) is a type of inflammatory skin disease caused by genetics, immune system dysfunction, and environmental stresses. It is, however, still considered to be a refractory disease. Macrophages are inflammatory immune cells that infiltrate the skin and induce inflammation. We investigated the effect of refined deep-sea water (RDSW) on lipopolysaccharide (LPS)-induced inflammatory response in RAW 264.7 macrophage cells. The results showed that RDSW suppressed the expressions of inducible nitric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 39 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…The activity of AP-1 was regulated at the expression level and post-translation modification via phosphorylation and dephosphorylation. 30,31) The activated AP-1 was translocated to the nucleus and bound to a DNA consensus sequence. Many agents that can reduce AP-1 activity have been shown to suppress inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of AP-1 was regulated at the expression level and post-translation modification via phosphorylation and dephosphorylation. 30,31) The activated AP-1 was translocated to the nucleus and bound to a DNA consensus sequence. Many agents that can reduce AP-1 activity have been shown to suppress inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…40 Furthermore, DSW has been reported to possess beneficial effects by regulating the MAPK pathway. 41,42 We found that the consumption of DSW significantly inhibited the phosphorylation of P38 MAPK in STZ-induced diabetic rat hearts ( Figure 2). From these results, P38 MAPK signaling was identified as an intracellular mechanism that mediates the antiinflammatory effects of DSW in heart tissues of STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, treatment of macrophages with a combination of Bay 117082 and extract or MgCl 2 synergistically inhibited IL-6 and TNF expression by LPS challenge, compared with treatment with Bay 117082 alone, which indicates that there are other transcription factors (TFs) affected by magnesium. The MAPK pathway, including p38, ERK, and JNK, is another important pathway downstream of TLR-4 to regulate activator protein 1 (AP-1) translocation into the nucleus, thereby enhancing inflammatory cytokine expression (41). Thus, we next investigated the activity of MAPK in the presence of extract and MgCl 2 .…”
Section: Resultsmentioning
confidence: 99%